TIME OF BLOOD PRESSURE IN TARGET RANGE IN ACUTE ISCHEMIC STROKE. (June 2022) - Kakaletsis, Nikolaos; Ntaios, George; Milionis, Haralampos; Protogerou, Athanasios; Karagiannaki, Anastasia; Chouvarda, Ioanna; Dourliou, Vasiliki; Ladakis, Ioannis; Kaiafa, Georgia; Daios, Stylianos; Doumas, Michael; Savopoulos, Christos
Abstract : Objective: The management and the prognostic role of blood pressure (BP) during the acute phase of acute ischemic stroke (AIS) still remain controversial. Time in target range (TTR) of BP was recently introduced and is suggested that reflects both patient's mean BP levels and the magnitude of BP variability (BPV). The purpose of this study is to investigate the association of blood pressure TTR derived from 24-hour ambulatory BP monitoring (ABPM), during the acute phase of AIS, with the severity of stroke and its predictive value for the 3 months outcome. Design and method: A total of 228 AIS patients (175 without prior disability) underwent ABPM every 20 minutes within 48 hours from onset using an automated oscillometric device (TM 2430, A&D Company Ltd). Clinical and laboratory findings were recorded. Mean BP parameters, BPV (standard deviation) and TTR for systolic (SBP), diastolic (DBP) and mean arterial pressure (MAP) were calculated. Endpoints were death and disability/death at 3 months. Results: A total of 14, 942 BP measurements were recorded ( 66 per AIS patient) within 72 hours of stroke onset. Patient's 24-hour blood pressure TTR was 34.7 ± 29.9%, 64.3 ± 24.2% and 55.3 ± 29.4% for SBP, DBP and MAP respectively. TTR of DBP and MAP differed according to stroke severity with a "J'' association in all AIS patents. In patients without prior hypertension, TTR was lower as stroke severity increased for both DBP (p = 0.031) and MAP (p = 0.016). In 175 patients without prior disability, increase in TTR of DBP and MAP associated significantly with a decreased risk of disability/death in the unadjusted and fully adjusted models (HR: 0.96, 95% CI: 0.95–0.98, p = 0.001 and HR: 0.97, 95% CI: 0.95–0.98, p = 0.001). Increase in SBP TTR was associated significantly with an increased risk of disability/death in fully adjusted model with the addition of mean SBP (HR: 1.03, 95% CI: 1.00–1.07, p = 0.047). Conclusions: TTR can be included for a more detailed description of BP course, according to stroke severity, and for the evaluation of BP predictive role, in addition to mean BP values, derived from ABPM during the acute phase of AIS.